Characterization of Phytophthora pistaciae, the causal agent of pistachio gummosis, based on host range, morphology, and ribosomal genome - Zahra MIRSOLEIMANI; Reza MOSTOWFIZADEH-GHALAMFARSA (Phytopathologia Mediterranea, 2013)
Gummosis is the most important disease of pistachio trees in Iranian pistachio orchards. Phytophthora pistaciae, the main causal agent of this disease, was isolated and described from Kerman province of Iran for the first time. The present study aimed to establish the host range, morphological characteristics and ribosomal genome of P. pistaciae isolates. During 2009–2010, isolates of P. pistaciae were sampled from 12 infected pistachio plantations in Kerman and Yazd provinces of Iran. Based on phylogenetic analysis of ITS regions, all isolates belonged to a monophyletic clade and clustered with P. pistaciae from other studies. The isolates were high temperature tolerant and produced non-papillate, ellipsoid to ovoid sporangia with polar caps, and were non-caducous, sympodial and had internal and external proliferation. The isolates were homothallic and produced spherical oogonia with smooth walls and paragynous, rarely amphigynous, spherical to ovoid antheridia. Oospores were spherical, colorless and aplerotic. Isolates generated chlamydospores in host tissues. The host range of P. pistaciae is not limited to pistachio species. Almond, walnut, apricot, grape, mango, sour cherry, among woody plants, and pea, different types of beans, chickpea, faba bean, safflower and okra, among herbaceous plants, were shown to be potential hosts of the pathogen. This study showed that isolates of P. pistaciae were homogenous in ITS rDNA genome and their host range, and morphological traits were similar.